Worldwide Status of Insecticide Resistance of Aedes aegypti and Ae. albopictus, Vectors of Arboviruses of Chikungunya, Dengue, Zika and Yellow Fever - Tahereh Sadat Asgarian; Hassan Vatandoost; Ahmad Ali Hanafi-Bojd; Fatemeh Nikpoor (Tehran University of Medical Sciences, 2023)
Background: Controlling of Aedes aegypti and Ae. albopictus, vectors of five important mosquito-borne diseases, is known as the most effective method to prevent the transmission of arboviruses to humans, but the emergence of insecticide resistance is threat for control and prevention of vector borne diseases. A better understanding of mosquito resistance to insecticides will help to develop more effective methods to control insecticide resistance in mosquito vectors. Methods: Worldwide geographical distribution of insecticide resistance in Ae. aegypti and Ae. albopictus by the available papers and map of the data for carbamates, organochlorines, organophosphates, pyrethroids, microbial and insect growth regulator insecticides were reviewed. Article data published up to December 2022 were investigated by searching the following databases: "Google Scholar", "PubMed", "Scopus", "SID" and "Web of Knowledge". Results: The results showed that the susceptibility and resistance status of Ae. aegypti and Ae. albopictus to insecticides in the world is very diverse. Conclusion: Due to the importance of Ae. aegypti and Ae. albopictus in the transmission of mosquito-borne arboviruses, resistance management should be given more attention worldwide to prevent insecticide resistance in the arbovirus vector and replace the new approach for vector control.